Genomic and Non-genomic Action of Neurosteroids in the Peripheral Nervous System - Colciago, Alessandra; Bonalume, Veronica; Melfi, Valentina; Magnaghi, Valerio (Frontiers in Neuroscience, 2020)
Since the former evidence of biologic actions of neurosteroids on the central nervous system, also the peripheral nervous system (PNS) was reported as a structure affected by these substances. Indeed, neurosteroids are synthesized and active in the PNS, exerting many important actions on the different cell types of this system. PNS is a target for neurosteroids, in their native form or as metabolites. In particular, old and recent evidence indicates that the progesterone metabolite allopregnanolone possesses important functions in the PNS, thus contributing to its physiologic processes. In this review, we will survey the more recent findings on the genomic and non-genomic actions of neurosteroids in nerves, ganglia, and cells forming the PNS, focusing also on the mechanisms regulating the peripheral neuron-glial crosstalk. Then we will refer to the physiopathological significance of the neurosteroid signaling disturbances in the PNS, in order to identify new molecular targets for feasible pharmacotherapeutic approaches.